Kesaksian Orang Bisu dalam Perspektif Hukum Indonesia dan Fikih: Tantangan, Peluang, dan Implikasi Terhadap Keadilan - Syahrul Hanafi; Ahmad Muhamad Mustain Nasoha; Arif Nurrohman; Ashfiya Nur Atqiya (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This article examines the testimony of mute individuals from the perspectives of Indonesian positive law and the comparative fiqh of the four major Islamic schools of thought (Hanafi, Maliki, Shafi’i, and Hanbali). The study aims to understand the challenges and opportunities in recognizing the testimony of mute individuals in court and its implications for justice. The research employs a normative approach with doctrinal analysis. The findings indicate that Indonesian positive law provides room for the testimony of mute individuals, but there are still obstacles in its implementation, such as the lack of adequate accommodations and qualified interpreters. On the other hand, Islamic fiqh presents varied views on mute testimony, with the Maliki school being more inclusive than others. The article also discusses opportunities for legal reform to create a more inclusive and just judicial system for persons with disabilities. In conclusion, the testimony of mute individuals requires special attention within the legal system to ensure that the principles of justice and equality are upheld.